PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X MAS PLUS PADANG GANTING KABUPATEN TANAH DATAR TAHUN PELAJARAN 2013/2014 - Eka Putri, Deni; Rismen, Sefna; Cesaria, Anna (Pendidikan Matematika, 2014)
ABSTRACTÂ Base on background knowledge of this research was studentsâ understanding of mathematical concept that still low and the material that students have was lost from their mind. This research is to determine whether studentsâ understanding of mathematical concept by using a strategy Hollywood square Review better than studentsâ understanding of mathematical concept by using conventional strategy at X Grade of MAS PLUS Padang Ganting. Type of this research was experiment. Population in this research was students at X grade of MAS PLUS Padang Ganting, and sample of this research was students class X1 as experimental class and X2 as control class. Post-test was as instrumentation in this research, with realibility 0,88.From the data analysis get mean score from studentsâ achievement in experimental class was 71.96 that highÂ  rather than in control class that was 48.57. data analysis was done by using hypothesis testing. Tcalculated= 3,6 and ttable= 1,68. so, we can conclude that studentsâ understanding of Â mathematical concept that used Hollywood Square Review better than conventional strategyÂ  at X Grade of MAS PLUS Padang Ganting.Â